Pengalaman Pemanfaatan Fasilitas Pelayanan Kesehatan pada Agregat Dewasa dengan Tuberculosis Paru - Ramadhana Ramadhana; Teuku Tahlil; Asniar Asniar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study explores the experience of using healthcare facilities in the aggregate of adults with pulmonary tuberculosis. The type of research used is qualitative research with a phenomenological approach. The study's results identified three themes: visiting healthcare facilities due to increased disease severity, visiting healthcare facilities to get further services, and visiting healthcare facilities despite being embarrassed and afraid. In conclusion, this study provides an overview of how the concept of the Health Belief Model about perceived severity makes a person with Pulmonary TB engage in Health Seeking Behavior, in this case, focusing on the desire to visit healthcare facilities. Keywords: Health Belief Model, Health Seeking Behavior, Pulmonary Tuberculosis